International virtual e-content development competition 2021 - Chua, Ang Lim (Faculty of Medicine, 2021)
The International Virtual E-Content Development Competition 2021 (e-ConDev 2021) was held virtually this year. Multiple faculty teams had joined in 3 categories: MOOC, Micro-credentials, and Open Education Resources (OER)- Educators.